Women Involved In Drug Dependence In Malaysia - A Preliminary Study. - Foong, K.; Navaratnam, Profesor Madya (Dr.) V.; Wong, P.C. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1987)

(untitled)
Over the period 1978 to 1986 a total of 1,272 women addicts are registered with the National Drug Abuse Monitoring System.